2013
DOI: 10.1051/mmnp/20138106
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Smooth Parseval Frames of Shearlets

Abstract: Abstract. The shearlet representation has gained increasing recognition in recent years as a framework for the efficient representation of multidimensional data. This representation consists of a countable collection of functions defined at various locations, scales and orientations, where the orientations are obtained through the use of shearing matrices. While shearing matrices offer the advantage of preserving the integer lattice and being more appropriate than rotations for digital implementations, the dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 31 publications
0
59
0
Order By: Relevance
“…Indeed, some basic ideas were already introduced in [41], where it was observed that there exist several ways to extend the shearing matrix to higher dimensions. A new construction yielding smooth Parseval frames of discrete shearlets in any dimensions was recently introduced in [37]. Several other results have also recently appeared, including the extension of the optimally sparse approximation results and the analysis and detection of surface singularities [10,33,34,35,36,54].…”
Section: Extensions and Generalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some basic ideas were already introduced in [41], where it was observed that there exist several ways to extend the shearing matrix to higher dimensions. A new construction yielding smooth Parseval frames of discrete shearlets in any dimensions was recently introduced in [37]. Several other results have also recently appeared, including the extension of the optimally sparse approximation results and the analysis and detection of surface singularities [10,33,34,35,36,54].…”
Section: Extensions and Generalizationsmentioning
confidence: 99%
“…This require to slightly modify the definition of the classical shearlet. Then the boundary shearlets are obtained, essentially, by piecing together the shearlets overlapping the boundary lines ξ 1 = ±ξ 2 which have been projected onto C and C. This modified construction yields smooth Parseval frames of band-limited shearlets and can be found in [37], where also the higher dimensional versions are discussed.…”
Section: Theorem 6 ([30]mentioning
confidence: 99%
“…[11] for details). For brevity, in the following we will denote the Parseval frame of 3D shearlets as…”
Section: D Shearletsmentioning
confidence: 99%
“…It turns out that the 3D system of shearlets is a Parseval frame of L 2 R 3 [6] and it provides essentially optimal approximations for functions of three variables which are C 2 regular away from discontinuities along C 2 surfaces [8].…”
Section: D Shearletsmentioning
confidence: 99%
“…Shearlets, in particular, offer a unique combination of very remarkable features: they have a simple and wellunderstood mathematical structure derived from the theory of affine systems [3,6]; they provide optimally sparse representations, in a precise sense, for a large class of images and other multidimensional data where wavelets are suboptimal [7,8]; and the directionality is controlled by shear matrices rather than rotations. This last property, in particular, enables a unified framework for continuum and discrete setting since shear transformations preserve the rectangular lattice and is an advantage in deriving faithful digital implementations [9,10].…”
Section: Introductionmentioning
confidence: 99%